Band-tail states meditated visible-light-driven overall water splitting in Y2Ti2O5S2 photocatalyst. Issue 45 (8th November 2022) - Li, Ronghua; Zha, Zhengdi; Zhang, Yanning; Yang, Minji; Lin, Lihua; Wang, Qian; Hisatomi, Takashi; Nakabayashi, Mamiko; Shibata, Naoya; Domen, Kazunari; Li, Yanbo
Abstract : Photoluminescence studies reveal the existence and double-edged sword role of band-tail states in the Y2 Ti2 O5 S2 photocatalyst, which prolong carrier lifetime, but prevent effective separation of the photogenerated electron–hole pairs. Abstract : Oxysulfide photocatalyst Y2 Ti2 O5 S2 is a narrow bandgap semiconductor that achieves overall water splitting via one-step photoexcitation under a wide range of solar spectrum (<640 nm). However, the photophysical properties that enable the visible-light-driven overall water splitting in Y2 Ti2 O5 S2 are not fully understood. Here, temperature/power-dependent and time-resolved photoluminescence spectroscopies reveal the transition of luminescence mechanism from exciton and free carrier recombination at low temperature to band-tail recombination at room temperature. Importantly, the band-tail states help to sustain a long carrier lifetime in Y2 Ti2 O5 S2, which is beneficial to achieving overall water splitting. Meanwhile, a high density of band-tail states may negatively affect photocatalytic activity due to the trap of photocarriers. Density function theory calculations reveal possible origins of the band-tail states, i.e., spatial potential fluctuations resulting from the random distribution of OS and SO antisites. Our findings reveal a new carrier management mechanism for photocatalysis that could guide the design of more efficient Y2 Ti2 O5 S2 photocatalyst.